Iodine deficiency disturbs the metabolic profile and elemental composition of human breast milk. (1st March 2022) - Arias-Borrego, A.; Velasco, I.; Gómez-Ariza, J.L.; García-Barrera, T.
Highlights: First metabolomic analysis of human breast milk of iodine deficient women. 31 metabolites were found altered in human milk of iodine deficient women. Se, Cu and Zn were significantly lower in human milk of iodine deficient women. Elements and metabolites could be used to predict iodine deficient lactating women. Abstract: Human breast milk (HBM) has a beneficial impact on health programming, growth and neurodevelopment of newborns. Increase in iodine intake is recommended for pregnant women in order to produce enough thyroid hormones to meet foetal requirements. In this work, a combined analytical multiplatform based on gas chromatography coupled to mass spectrometry and ultra-high performance liquid chromatography coupled to quadrupole-time-of-flight mass spectrometry has been applied in the first metabolomic study of HBM of iodine-deficient women. In addition, the elemental composition of HBM has been determined by inductively coupled plasma triple quadrupole mass spectrometry. Remarkably, 31 metabolites with important biological roles (e.g. glycerophospholipids for neurodevelopment) were seen to be altered in the HBM of iodine-deficient women. The main metabolic pathways altered include lipid metabolism, amino acid cycle, the tricarboxylic acid cycle and glycolysis. Additionally, the concentration of selenium, zinc and copper were seen to be significantly lower in HBM of iodine-deficient women.